Texting on mobile phones and musculoskeletal disorders in young adults: A five-year cohort study. (January 2017) - Gustafsson, Ewa; Thomée, Sara; Grimby-Ekman, Anna; Hagberg, Mats
Abstract: The aim was to examine whether texting on a mobile phone is a risk factor for musculoskeletal disorders in the neck and upper extremities in a population of young adults. In a longitudinal population-based cohort study with Swedish young adults (aged 20–24 years) data were collected via a web-based questionnaire at baseline (n = 7092) and after one and five years. Cross-sectional associations were found between text messaging and reported ongoing symptoms in neck and upper extremities (odds ratios, ORs 1.3–2.0). Among symptom-free at baseline prospective associations were only found between text messaging and new cases of reported symptoms in the hand/fingers (OR 2.0) at one year follow up. Among those with symptoms at baseline prospective associations were found between text messaging and maintained pain in neck/upper back (OR 1.6). The results imply mostly short-term effects, and to a lesser extent, long-term effects on musculoskeletal disorders in neck and upper extremities. Highlights: Associations between text messaging and symptoms in neck and upper extremities. Associations between text messaging and new cases of symptoms after one year. Associations between text messaging and maintained neck pain after one year.